2021
DOI: 10.1002/dad2.12241
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum urate and CSF markers of Alzheimer's disease pathology in a population‐based sample of 70‐year‐olds

Abstract: Introduction The relationship between urate and biomarkers for Alzheimer's disease (AD) pathophysiology has not been investigated. Methods We examined whether serum concentration of urate was associated with cerebrospinal fluid biomarkers, amyloid beta (Aβ) 42 , Aβ 40 , phosphorylated tau (p‐tau), total tau (t‐tau), neurofilament light (NfL), and Aβ 42 /Aβ 40 rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…CNS, central nervous system a median follow-up of 5 years, hazard ratios of developing AD among patients with gout were 0.71(95% CI, 0.62-0.80), and 0.76 (95% CI, 0.66-0.87) in univariate and multivariate analyses, respectively. 15 Finally, the current study by Fatima et al 8 appears to be consistent with the prior literature. 18,19 However, the employed analysis ushers in a much-needed discussion about research design to characterize the implications of urate production in the brain compared to systemically circulating urate levels as well as the role of the blood-brain barrier in urate transport.…”
Section: F I G U R Esupporting
confidence: 90%
See 2 more Smart Citations
“…CNS, central nervous system a median follow-up of 5 years, hazard ratios of developing AD among patients with gout were 0.71(95% CI, 0.62-0.80), and 0.76 (95% CI, 0.66-0.87) in univariate and multivariate analyses, respectively. 15 Finally, the current study by Fatima et al 8 appears to be consistent with the prior literature. 18,19 However, the employed analysis ushers in a much-needed discussion about research design to characterize the implications of urate production in the brain compared to systemically circulating urate levels as well as the role of the blood-brain barrier in urate transport.…”
Section: F I G U R Esupporting
confidence: 90%
“…Finally, the current study by Fatima et al. 8 appears to be consistent with the prior literature. 18 , 19 However, the employed analysis ushers in a much‐needed discussion about research design to characterize the implications of urate production in the brain compared to systemically circulating urate levels as well as the role of the blood–brain barrier in urate transport.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Several studies have examined the association of uric acid with AD from the neuropathological perspective, with contradictory findings. For example, a positive association between serum uric acid levels and CSF amyloid beta (Aβ) 42 was found in cognitively healthy men (β = 0.55, P = .04) [ 7 ]. Li and colleagues reported that serum uric acid levels were negatively correlated with CSF Aβ 42 levels among cognitively healthy older adults [e.i., individuals with highest uric acid (> 75% percentile) had lower CSF Aβ 42 levels relative to those with lowest uric acid (β = –5.1×10 −4 , p = 0.019)] [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some observational studies suggest that high UA levels may have deleterious effects on brain health, including the development of cerebral small vessel disease and cognitive decline [10,11]. However, studies have also indicated that serum UA plays a neuroprotective role in the diseases of Alzheimer's and Parkinson's and that low blood UA levels are not only associated with faster disease progression, but are also indicative of malnutrition [12][13][14][15]. Appropriate increases in UA levels within the normal range can instead delay the onset and progression of cognitive impairment [16].…”
Section: Introductionmentioning
confidence: 99%